XML Applications for study material markup in distance learning - Lesna, N.; Repka, V.; Sakalo, T. (ХНУРЭ, 2004)
The presented paper was written as a consequence of growing need for properly designed distance learning implementation. Scalable and exhaustive tool for description of learning materials was supposed to be a final result of this work. For this purpose, was researched the current situation in the area of markup techniques. The obvious conclusion was made that a special markup language definition is necessary to reach the given goals. This conclusion was also addressed within this research and the document type definition suitable for the given goals was designed. The proposed solution is based on the analysis of strengths and weaknesses of existing markup languages purposed for distance learning needs.